Anatomical Characterization and Elements Analysis of Native and Non-Native Senna Species in Qatar - Noof Fakhroo (23753019) (2025)
Senna, also referred to as Senna mekki or Ishriq, is a famous medicinal plant belonging to the Fabaceae family. It is a flowering plant that can reach a height of up to 2 m and is distinguished by its attractive yellowish-orange flowers. It comprises approximately 250 to 260 species, distributed worldwide. Senna plants are tough plants that can thrive in deserts, as well as tropical and subtropical areas, showing they're adaptable to stressful conditions like high temperatures and drought. Senna, considered an important medicinal plant that is utilized traditionally in the Arabian Gulf, is renowned for its ability to relieve constipation and various digestive system disorders. This study investigates the anatomical features of native and nonnative Senna in Qatar, analyzing the biochemical compounds of three species: S. italica, S. occidentalis, and S. alexandrina. Advanced instruments, such as Scanning Electron Microscopy (SEM), were used to examine the anatomical features, aiding in distinguishing and comparing native and non-native Senna at the anatomical level. Inductively coupled plasma optical emission spectroscopy (ICP-OES) is utilized to analyze trace elements in leaves, seeds, and soil through elemental analysis. The investigation highlights the significant differences between native S. italica and non-native S. occidentalis, mainly due to the presence of trichomes in the leaves, which are more plentiful in native species. Meanwhile, element analysis shows differences in element composition among the species in leaves, seeds, and soils. The findings provide evidence that native S. italica has unique anatomical features that enable it to thrive in arid regions. Additionally, it has higher levels of biochemical compounds that improve its ability to adapt and withstand harsh conditions in comparison to the introduced S. occidentalis and S. alexandrina. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx